2011
DOI: 10.1107/s0108768111033015
|View full text |Cite
|
Sign up to set email alerts
|

On the transferability of QTAIMC descriptors derived from X-ray diffraction data and DFT calculations: substituted hydropyrimidine derivatives

Abstract: The combined study of electron-density features in three substituted hydropyrimidines of the Biginelli compound family has been fulfilled. Results of the low-temperature X-ray diffraction measurements and density functional theory (DFT) B3LYP/6-311++G** calculations of these compounds are described. The experimentally derived atomic and bonding characteristics determined within the quantum-topological theory of atoms in molecules and crystals (QTAIMC) were demonstrated to be fully transferable within chemicall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 100 publications
(95 reference statements)
0
5
0
Order By: Relevance
“…[28,29,47] In these studies experimental values of the Laplacian were up to 1.3 a.u. higher than theory for C=O bonds and 0.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[28,29,47] In these studies experimental values of the Laplacian were up to 1.3 a.u. higher than theory for C=O bonds and 0.…”
Section: Resultsmentioning
confidence: 99%
“…Other studies on organic molecules also found only small differences between molecular and periodic boundary condition DFT calculations. [28,29] Parenthetically, we note that Vallet et al have previously studied the effect of environment on the electronic spectrum of the uranyl dication (UO 2…”
Section: Introductionmentioning
confidence: 81%
“…For example, we did not locate the critical point corresponding to the Cl•••Cl intermolecular interaction in the chlorokojic acid crystal; the Cl•••Cl contact in this crystal is characterized by D = 4.366 Å and ρ b < 0.003 au. 62 This value of the electron density is at the limit of the experimental accuracy that may be reached nowadays in experimental charge density analysis 119 or evaluated from the theoretical electron density of molecular crystals. 58 1 and S2) are approximately described by a single curve.…”
Section: Resultsmentioning
confidence: 99%
“…The HCTH407 (8) and B97-2 (9) functionals were fitted to reproduce the profile of nearly exact exchange-correlation potentials (and thereby densities) of some atomic and molecular systems. Electron densities produced by several DFT functionals have already been tested in various studies [ (10)(11)(12)(13)(14)(15) and references therein], but modern highly parameterized functionals were not included.…”
mentioning
confidence: 99%